PEMARKAH PERSUASIF PADA BAHASA MEDIA PUBLIKASI BAKAL CALON GUBENUR RIAU PERIODE 2018-2023 - Ali, Hamdan; Auzar, Auzar; Burhanuddin, Dudung (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The use of publicity media Prospective Candidate Governor of the Riau period 2018-2023 strongly assessed the candidate's goal of sitting in the chair they dreamed. Use of media publications that are often encountered, such as banners, billboards, on social media. Media publications are not spared from using convincing marker. The use of markers is essential for optimizing campaign sending messages. The aim of this study is to determine what marker and meaning contains in the media publication candidate governor of Riau period 2018-2023. The type of research used is qualitative research. Used techniques for data collection are documentation techniques. The first step is to take photos of banners, billboards and screenshots of electronic media containing the publication of the Governor Candidate Riau Candidate. Secondly, look up the publishing media that is supposed to have the same content. The results indicate that there is a convincing marker in the language of the publishing media candidate governor of Riau. First, the claim is a statement with a convincing purpose, divided into two, ie an explicit claim (contains a solemn invitation) and an implicit claim (which contains a call in secret). Secondly, the warrant is a statement that has been packaged in the form of an invitation or persuasion and is not impressed being forced to elect the candidate governor. Third, convincing data based on data or facts to reinforce the argumentation of the Governor Candidate's message. It is not enough to understand the convincing meaning of the publication media, but it sometimes requires us to understand more deeply in terms of meaning and context. Indirect meanings will be more difficult to interpret than direct intentions. That is why the opponent has to worry about the context surrounding the speech.Keywords: marker, persuasive, media